Conceptual directions of optimization psychiatric care to population of advanced and elderly age - Klimenko, V. I.; Dikhtyar, A. Yu. (Zaporozhye Medical Journal, 2013)
This article proved that conceptual directions of optimization psychiatric care to population of advanced and elderly age in conditions of reform of general Ukraine’s health system must attract physicians of primary health care to identify those persons who have risk factors or already have changes in mental health according with data of conducted screening to further address to doctors of psychiatric service.